2018
DOI: 10.1088/1748-9326/aab63c
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions could reduce the blue carbon value of marshes on eutrophic estuaries

Abstract: The supply of nitrogen to ecosystems has surpassed the Earth's Planetary Boundary and its input to the marine environment has caused estuarine waters to become eutrophic. Excessive supply of nitrogen to salt marshes has been associated with shifts in species' distribution and production, as well as marsh degradation and loss. Our study of salt marshes in agriculturally intensive watersheds shows that coastal eutrophication can have an additional impact. We measured gas fluxes from marsh soils and verified emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Static chamber measurements are thus often taken during low tide when nutrient concentrations and N 2 O fluxes are likely to be lower ( Adams, Andrews & Jickells, 2012 ). Roughan et al (2018) found N 2 O flux varied with the tidal cycle and observed the highest N 2 O fluxes immediately after the high tide receded. Simply using an average of high tide and low tide fluxes extrapolated over 24 hours may thus overestimate or underestimate daily N 2 O fluxes ( Roughan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Static chamber measurements are thus often taken during low tide when nutrient concentrations and N 2 O fluxes are likely to be lower ( Adams, Andrews & Jickells, 2012 ). Roughan et al (2018) found N 2 O flux varied with the tidal cycle and observed the highest N 2 O fluxes immediately after the high tide receded. Simply using an average of high tide and low tide fluxes extrapolated over 24 hours may thus overestimate or underestimate daily N 2 O fluxes ( Roughan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 86%
“… Roughan et al (2018) found N 2 O flux varied with the tidal cycle and observed the highest N 2 O fluxes immediately after the high tide receded. Simply using an average of high tide and low tide fluxes extrapolated over 24 hours may thus overestimate or underestimate daily N 2 O fluxes ( Roughan et al, 2018 ). To accurately model the soil’s response to flooding, it is important to verify the effect of flooding on N 2 O emissions at high tide, low tide, and mid tide (halfway between high tide and low tide).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Methane and nitrous oxide are released by microbial decomposition of organic matter, and are influenced by conditions such as temperature, salinity, and the amount of organic matter. Methane emissions tend to be more pronounced where salinity is low, but can sometimes be high in mangrove and tidal marsh ecosystems (Rosentreter et al, 2021), while nitrous oxide emissions can be high in places where nitrogen inputs have been substantial (Roughan et al, 2018). Methane emissions in seagrasses tend to be low, and although nitrous oxide emissions can sometimes be high, one study showed that net abatement of seagrass restoration was still substantial (Oreska et al, 2020).…”
Section: Leakagementioning
confidence: 99%